Occurrence of Strongyloides stercoralis in Yunnan Province, China, and comparison of diagnostic methods. - Peter Steinmann; Xiao-Nong Zhou; Zun-Wei Du; Jin-Yong Jiang; Li-Bo Wang; Xue-Zhong Wang; Lan-Hua Li; Hanspeter Marti; Jürg Utzinger (Public Library of Science (PLoS), 2007)
BACKGROUND: Strongyloides stercoralis is a neglected soil-transmitted helminth species, and there is a lack of parasitologic and epidemiologic data pertaining to this parasite in China and elsewhere. We studied the local occurrence of S. stercoralis in a village in Yunnan province, China, and comparatively assessed the performance of different diagnostic methods. METHODOLOGY/PRINCIPAL FINDINGS: Multiple stool samples from a random population sample were subjected to the Kato-Katz method, an ether-concentration technique, the Koga agar plate method, and the Baermann technique. Among 180 participants who submitted at least 2 stool samples, we found a S. stercoralis prevalence of 11.7%. Males had a significantly higher prevalence than females (18.3% versus 6.1%, p = 0.011), and infections were absent in individuals <15 years of age. Infections were only detected by the Baermann (highest sensitivity) and the Koga agar plate method, but neither with the Kato-Katz nor an ether-concentration technique. The examination of 3 stool samples rather than a single one resulted in the detection of 62% and 100% more infections when employing the Koga agar plate and the Baermann technique, respectively. The use of a mathematical model revealed a 'true' S. stercoralis prevalence in the current setting of up to 16.3%. CONCLUSIONS/SIGNIFICANCE: We conclude that S. stercoralis is endemic in the southern part of Yunnan province and that differential diagnosis and integrated control of intestinal helminth infections needs more pointed emphasis in rural China.